Variation of morphological features and growth traits in half sib baby calves of Pabna cattle in Bangladesh - Talukder, Md Azharul Islam; Shahjahan, Md; Munira, Sirazum; Rahman, Seikh Masudur; Ali, Md Yousuf; Salahuddin, Md; Miah, Md Abu Haris; Billah, Md Mostain; Habib, Md Rezwanul; Bhuiyan, Abul Kashem Fazlul Haque (Asian Journal of Medical and Biological Research, 2019)
This study was aimed to identify the phenotypic features of local Pabna calves including their growth trait attributes at BLRI Regional Station, Baghabari. Data on different phenotypic measurements and growth traits were collected from 12 half sib Pabna baby calves. Each calf was allowed to drink 10% of milk for individual’s body weight from respective dam. Data analyses were conducted following independent sample t-test and one-way ANOVA using SAS 9.1.3 (SAS Institute Inc., Cary, NC, USA). Although significant differences observed in body weight (p<0.001), body length (p<0.05), heart girth (p<0.05) and mouth circumference (p<0.05) based on two types of birth weight groups in calves (<20 kg and ≥20 kg) but there were limited effects observed in the baby calves at three months except head length (p<0.05) considering dam’s body weights. Observed growth rate has no variations (p>0.05) in baby calves. This study revealed that half sib calves originated from the same sire had similar morphological features and growth in the early stage while dams’ body weight had limited effects on those aspects. Asian J. Med. Biol. Res. March 2019, 5(1): 52-55